Alkaloid-induced asymmetric hydrogenation on bimetallic Pt@Cu cathodes under electrochemical conditions. (20th July 2017) - Yue, Ying-Na; Wu, Di; Zeng, Sheng; Yang, Man-Ping; Wang, Huan; Lu, Jia-Xing
Abstract : Pt@Cu NPs were coated on carbon paper and used as a cathode for asymmetric electrohydrogenation of pro-chiral aromatic ketones catalyzed by cinchonidine (CD) alkaloids. Abstract : Bimetallic Pt@Cu nanoparticles (NPs) with low Pt loading obtained by reducing platinum precursors on Cu NPs were coated on carbon paper and used as a cathode for asymmetric hydrogenation by the electrochemical method. The Pt@Cu NPs exhibited enhanced catalytic performance in ketone electrohydrogenation. The enantioselective electrohydrogenation of pro-chiral aromatic ketones (2, 2, 2-trifluoroacetophenone, acetophenone, 2-phenylacetone, 4-methylacetophenone) induced by cinchonidine alkaloids was investigated in an undivided cell to obtain optically active alcohols. Optically active α-(trifluoromethyl)benzyl alcohols with 59% enantiomeric excess and 25% yield were obtained. All experimental procedures were performed under mild conditions, that is, without the utilization of high temperature and pressure. The Pt@Cu NPs showed excellent stability and reusability.